Bismuth(III) Triflate-Catalyzed Intermolecular Cyclization of Phenols with Diols: Direct Access to O-Heterocycles - Minakawa, Maki; Sakurai, Yuya (Synlett, 2022)
A direct access to O-heterocycles by Bi(OTf)3-catalyzed intermolecular cyclization of phenols with diols is described. Catalytic dehydrative tandem formation of C–O and C–C bonds was achieved by using a Bi(OTf)3 catalyst without any additives. The catalytic intermolecular cyclization of phenols with various diols proceeded to give the corresponding chromanes in up to 91% yield and/or pyran derivatives in up to 66% yield.
Keywords: phenols; diols; bismuth catalysis; cyclization; chromanes; pyrans